Anthropogenic and Sediment Controls on TPH in Tigris Sediments - Altaf Raheem Shnaishel; Hamza Abdulhassan Kadim; Hamid T. AL-Saad (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Petroleum hydrocarbons are persistent aquatic contaminants that accumulate in sediments and serve as records of environmental pollution. Specific Background: The Tigris River in Maysan Governorate faces increasing hydrocarbon inputs associated with urbanization, industrial discharge, and riverine processes. Knowledge Gap: Limited integrated assessments have examined the vertical and spatial distribution of Total Petroleum Hydrocarbons (TPHs) alongside Total Organic Carbon (TOC) and sediment grain size within core sediments of this river system. Aim: This study investigates the distribution patterns of TPHs and their relationships with TOC and sediment texture across seven stations (0–50 cm depth). Results: TPH concentrations ranged from 4.49 to 114.13 µg/g, with the highest values at Al-Amara and Ali Al-Sharqi linked to anthropogenic sources. Fine-grained sediments (silt and clay >70%) corresponded with higher TOC (1.66–10.73%), while correlation analysis showed weak association between TPH and TOC but strong relationships between TOC and fine fractions. Novelty: The study integrates vertical profiling and sedimentological controls to distinguish anthropogenic inputs from natural retention mechanisms. Implications: Findings support targeted monitoring and sediment management strategies in hydrocarbon-affected river systems. Highlights: Anthropogenic proximity governs peak hydrocarbon accumulation. Fine-grained sediments regulate organic matter retention. Vertical cores document historical contamination layers. Keywords: Total Petroleum Hydrocarbons, Tigris River, Sediment Core, Total Organic Carbon, Grain Size